Evaluación de las Redes Neuronales Artificiales Perceptron Multicapa y Fuzzy-Artmap en la Clasificación de Imágenes Satelitales - Toro Bayona, Guillermo Antonio; Lizarazo Salcedo, Iván Alberto (Ingeniería, 2012)
In this paper a quantitative and qualitative comparison between performance of Multilayer Perceptron and Fuzzy-Artmap neural networks for classification of land cover from multispectral satellite images is reported. It describes parameters and conditions that help to produce accurate classified images. Additionally, it makes a comparison between the two types of neural networks models describing both their advantages and disadvantages.